Progressive Law Paradigm in Islamic Family Law Renewal in Indonesia - Fauzan Fauzan (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
This paper discusses the progressive legal paradigm in renewal Islamic family law in Indonesia. Starting from the complexity of family problems in the contemporary era, the presence of progressive legal thinking is one of the foundations in order to provide certainty and justice in society. The results of this study indicate that legal reform progressive in the field of Islamic family law can be noticed from law enforcement through court decisions. Various judges’ decisions have created jurisprudence and are used as guidelines for Religious Court judges in deciding cases. This can be seen from the decisions of the constitutional justices, including regarding the restrictions on polygamy, the status of children out of wedlock and the age of marriage which was later successfully revised with the issuance of Law 16 of 2019 concerning Amendments to Law 1 of 1974 concerning Marriage. In the context of progressive legal reform in Indonesia, judges use reinterpretation of religious texts (fiqh), and understand the social context of modern society dynamics. For this reason, judges are required to be more courageous not only to be bound textually, but also to put forward the goal of realizing justice and benefit in the midst of society. Thus, the main legal objectives will be realized, namely substantive justice, benefits, and legal certainty because the law is basically for humans, not for the law itself